2004
DOI: 10.1097/01.asn.0000146012.44570.20
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and the Risk of Incident Kidney Stones in Men

Abstract: Abstract. Diet plays an important role in the pathogenesis of kidney stones. Because the metabolism of many dietary factors, such as calcium, may change with age, the relation between diet and kidney stones may be different in older adults. Uncertainty also remains about the association between many dietary factors, such as vitamin C, magnesium, and animal protein, and the risk of kidney stone formation. To examine the association between dietary factors and the risk of incident, symptomatic kidney stones in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
301
5
24

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(339 citation statements)
references
References 43 publications
9
301
5
24
Order By: Relevance
“…Our study shows that higher nondairy animal protein intake and lower potassium intake are independently associated with lower urinary citrate excretion at the population level and supports the simultaneous implementation of both dietary animal protein restriction and increased intake of fruits and vegetables for SFs with lower urinary citrate. In previous studies, we reported an increased risk of nephrolithiasis among men with higher vitamin C intake, which was proposed to result from higher vitamin C intake leading to higher urinary oxalate excretion (46). The fact that vitamin C is associated with low urinary citrate excretion in men may represent an alternative explanation for the observed increased risk of stone formation.…”
Section: Discussionmentioning
confidence: 81%
“…Our study shows that higher nondairy animal protein intake and lower potassium intake are independently associated with lower urinary citrate excretion at the population level and supports the simultaneous implementation of both dietary animal protein restriction and increased intake of fruits and vegetables for SFs with lower urinary citrate. In previous studies, we reported an increased risk of nephrolithiasis among men with higher vitamin C intake, which was proposed to result from higher vitamin C intake leading to higher urinary oxalate excretion (46). The fact that vitamin C is associated with low urinary citrate excretion in men may represent an alternative explanation for the observed increased risk of stone formation.…”
Section: Discussionmentioning
confidence: 81%
“…The risk of stone development was elevated by 17% among women randomized to calcium and vitamin D supplements versus placebo in women's health initiative study (2) and by 20% in the nurse's health study I (3). On the other hand, other studies such as nurse's health study II and the health professionals follow up study revealed the absence of an association between calcium supplements intake and kidney stones development (12)(13)(14). Hence, patients with nephrolithiasis should be counseled to increase their dietary calcium resources and to routinely monitor their urine if they are using calcium supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment costs are high (7,8). Epidemiological studies have linked stone disease to obesity, metabolic syndrome, and also to fluid, protein and salt intake (9)(10)(11). Lifestyle changes, dietary strategies and medical therapy have been shown to reduce recurrence (12).…”
Section: Introductionmentioning
confidence: 99%